1966
DOI: 10.1002/pssb.19660180102
|View full text |Cite
|
Sign up to set email alerts
|

Feldkathoden mit dünnen Isolatorschichten

Abstract: Inhsltsiibersicht 1. Einleitung 2. Der Malter-Effekt und die feldabhangige Sehndarelektronenemission 3. Spike, rnit dunnen Isolierschichten bedeckte Kathoden 4. Sandwich-Kathoden 4.1 Konstruktion und Materialien 4.2 Kathoden mit Dielektrikumsdicken d < 100 A 4.3 Kathoden mit Dielektrikumsdicken d zwischen M 100 A und 1 pm 4.4 Kathoden rnit Dielektrikumsdicken d 2 1 pm wich-Kathoden 5.1 Prozesse an der Barriere Metal1 1 -Dielektrikum 5.2 Prozesse im Dielektrikum 5.3 Prozesse in der oberen Elektrode 5.4 Emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1969
1969
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…Furthermore, it has also been reported that electroformed oxide layers can emit electrons into the vacuum [11]. The latter observations show that an electroformed oxide layer on a metal can dramatically alter the work function of the underlying metal [39,40].…”
Section: Electroluminescence and Filament Modelmentioning
confidence: 87%
“…Furthermore, it has also been reported that electroformed oxide layers can emit electrons into the vacuum [11]. The latter observations show that an electroformed oxide layer on a metal can dramatically alter the work function of the underlying metal [39,40].…”
Section: Electroluminescence and Filament Modelmentioning
confidence: 87%
“…A voltage of 3 V applied across a 20 A domain creates a field strength of 1. 5 x 107 V/cm. An average breakdown field strength of 8x lo6 V/cm is calculated for an oxide thickncss of 50 A and a breakdown voltage of 4 V. These field strengths are much higher than those of the best bulk insulators of 3 x lo6 V/cm.…”
Section: Discussionmentioning
confidence: 99%
“…33 Research on electron emission in low temperature Al 2 O 3 cathodes has indicated the importance of ionized defects in the oxide. 34 Therefore both the electroluminescence and electron emission from the Al 2 O 3 memory diodes during operation clearly indicate the importance of ionization and charge recombination at defects in the oxide. The oxygen vacancy defects that have been proposed to play an active role in the resistive switching have levels that lie within the gap of the pristine insulating material.…”
Section: Electroluminescence In Al 2 O 3 /Polymer Resistive Switchmentioning
confidence: 97%